Knowledge and attitude towards the Middle East respiratory syndrome coronavirus among healthcare personnel in the southern region of Saudi Arabia - Huda F. Abbag; Awad A. El-Mekki; Ali A. Ali Al Bshabshe; Ahmed A. Mahfouz; Ahasen A. Al-Dosry; Rasha T. Mirdad; Nora F. AlKhttabi; Lubna F. Abbag (Elsevier, 2018)
Introduction: Middle East respiratory syndrome coronavirus (MERS-CoV) belongs to the family Coronaviridae, and is named for the crown-like spikes on its surface. The clinical presentation of MERS-CoV infection ranges from asymptomatic to very severe disease, and the classical presentation includes fever, cough chills, sore throat, myalgia, and arthralgia. Methods: A cross-sectional study of 339 healthcare personnel was conducted over an 8-month period in the Aseer region of Saudi Arabia using a structured survey that included demographic information and questions testing participant's knowledge. Results: Approximately two-thirds of the respondents properly identified the causative agent of MERS-CoV as an RNA virus (66.4%, n = 225) that is enveloped (68.1%, n = 231). On the other hand, few respondents identified the proper number of strains or the genus (16.5% and 17.4%, respectively). More than half of the study sample identified the disease as zoonotic (57.2%, n = 194). Similarly, 89.1% (n = 302) identified that camels and bats are prone to infection with coronaviruses. Only 23.9% (n = 81) properly identified March through May as the season with the highest transmission rate. There was a massive lack of adequate knowledge regarding prevalence of antibodies. Only 18.3% (n = 62) of respondents identified PCR as the proper diagnostic confirmatory test for MERS-CoV infection. Regarding MERS-CoV clinical features, 76.4% (n = 259) recognized the presence of sub-clinical infection, 64.7% (n = 218) indicated that cases should be immediately isolated, and 46.9% (n = 159) identified the main cause of mortality as respiratory failure. Conclusions: There is limited microbiological and virological knowledge of MERS-CoV infection among healthcare personnel in the southern region of Saudi Arabia, although the clinical aspects are known. Keywords: Knowledge, Attitude, Middle East respiratory syndrome, Coronavirus, Healthcare personnel